ANALISIS KEMAMPUAN BERPIKIR REFLEKTIF SISWA SMP DI KOTA CIMAHI PADA MATERI OPERASI ALJABAR DITINJAU DARI SELF REGULATED - Reyna Suhartina; Muhammad Salimul Farhan; Kushendri Kushendri; Adi Nurjaman (Journal on Education, 2019)
Mathematical reflective thinking ability is a process of thinking someone in understanding, identifying, analyzing problems based on relevant information and determining solutions to solve these problems. The importance of reflective marriage is to help students develop high-level thinking skills through their encouragement to: 1) connect new knowledge to their previous understanding. 2) thinking in abstract and concrete terminology. 3) apply specific strategies for new tasks. 4) understand their own thinking processes and learn on their own. The research method used is descriptive qualitative. The population of this study was all junior high school students in the city of Cimahi, which became the sample of this study were students of class VII-H at Cimahi Middle School 8. The instruments of reflective thinking ability were given to students as many as 5 questions for written tests accompanied by interviews with each student. Then the results obtained are the level of mathematical reflective thinking ability of junior high school students in Cimahi City based on written tests and the results of interviews with Cimahi students are still relatively low and there is no influence between student self-independence and mathematical relative thinking skills.